Dynamics of movement: Intensity, ritualized play and the cosmology of kinship relations in Northeast Brazil. (June 2020) - Shapiro, Matan
Relations between play and ritual are notoriously problematic. While play tends to produce doubt, uncertainty and paradox, ritual instead clarifies, authenticates and refines the moral order. Focusing ethnographically on a celebration for the Divine Holy Spirit ( Divino Espírito Santo ) in the Brazilian state of Maranhão, in this article I nonetheless move away from this common juxtaposition of ritual and play as mutually exclusive conceptual frameworks. I argue that we can instead imagine play and ritual as dynamic, processual experiences, which frequently merge when they are enacted together in highly symbolic public events. Seen in this light, ritual and play do not necessarily differ as rigid, predefined, conceptual frames, but rather as experiences that unfold in different forms: the experiential dynamic of play-scenarios is felt as horizontal deregulation, while the experiential dynamic of rituals converges towards and linear hierarchization. I consequently suggest more broadly that such dynamic terms as 'pulsation', 'intensity' and 'rhythm' better explicate the enduring social effects of public events in which the unequivocal and the ambiguous incessantly reconstitute each other.